INDUCED INSTABILITY IN INTERPHASE BOUNDARIES THERMOMIGRATION - Vladimir Lozovskij; Vladimir Lozovskij; Leonid Lunin; Boris Seredin; Igor Sysoev (Вестник Северо-Кавказского федерального университета)
The article describes a method of detecting the predicted theoretically transfer local perturbation effect on one of the interface flat liquid zone to another when it thermomigration in the crystal. The results of experimental studies of the features of the induced perturbation and its impact on the stability of the flat zone as a whole. It was found that the effect of induced instability could be the basis for a method of forming semiconductor wafers in volume of regular structures in the form of bands of deep electron-hole transitions and through the conducting channels. A method of using induced instability effect for silicon device structures.